2020
DOI: 10.1007/s10803-020-04489-1
|View full text |Cite
|
Sign up to set email alerts
|

Early Motor Differences in Infants at Elevated Likelihood of Autism Spectrum Disorder and/or Attention Deficit Hyperactivity Disorder

Abstract: We investigated infant's manual motor behaviour; specifically behaviours crossing the body midline. Infants at elevated likelihood of Autism Spectrum Disorder (ASD) and/or Attention Deficit Hyperactivity Disorder (ADHD) produced fewer manual behaviours that cross the midline compared to infants with a typical likelihood of developing these disorders; however this effect was limited to 10-month-olds and not apparent at age 5 and 14 months. Although, midline crossing did not predict ASD traits, it was related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 136 publications
(129 reference statements)
0
14
0
1
Order By: Relevance
“…Our account also has implications for developmental disorders in which either the sensory input, or the ability to integrate multisensory signals may differ. For example, a recent longitudinal study that investigated midline crossing behaviours showed that at 10 months of age (but not at five and 14 months), infants at risk of ASD or ADHD produced fewer manual actions that involved their hand crossing the body midline into the contralateral side of space compared to low-risk infants [86]. This reduced level of midline crossing may play a role in the recently demonstrated delay in the ability to represent touch across body postures in children with ASD [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…Our account also has implications for developmental disorders in which either the sensory input, or the ability to integrate multisensory signals may differ. For example, a recent longitudinal study that investigated midline crossing behaviours showed that at 10 months of age (but not at five and 14 months), infants at risk of ASD or ADHD produced fewer manual actions that involved their hand crossing the body midline into the contralateral side of space compared to low-risk infants [86]. This reduced level of midline crossing may play a role in the recently demonstrated delay in the ability to represent touch across body postures in children with ASD [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…STAARS is an ongoing longitudinal study following the development of infants who either have a first-degree relative with a diagnosis or probable research diagnosis of ADHD, and/or a diagnosis of ASD (and thus are at elevated likelihood of ADHD), or who have no family history of ADHD and ASD (and thus are at typical likelihood of ADHD). We had originally preregistered analyses to be conducted with infants at typical likelihood of ADHD and infants with a family history of ADHD only; however, in line with current moves towards transdiagnostic approaches in studying the early development of neurodevelopmental conditions [ 43 , 74 ] we subsequently expanded our analysis to include an additional cohort of infants with a family history of ASD. Infants with a family history of ASD are also at elevated likelihood of ADHD [ 10 ], and for autistic individuals, ADHD symptoms can impact outcomes [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study design leverages the fact that ADHD is highly heritable, with increased prevalence in individuals with first degree relatives with ADHD [ 37 , 38 ] or ASD [ 39 , 40 ]. Several research groups have launched prospective longitudinal studies to understand early manifestations of ADHD liability in infants with a family history of ADHD [ 41 , 42 , 43 , 44 ] or ASD [ 45 ]. This body of work has often concentrated on two domains of early functioning that, as discussed above, are linked to ADHD symptoms: focused attention and elevated activity level.…”
Section: Introductionmentioning
confidence: 99%
“…Second, although biomarkers (e.g., EEG, MRI) may potentially be more sensitive to group differences before behavioral differences are evident (Bosl et al, 2018;Shen et al, 2013Shen et al, , 2017Emerson et al, 2017;Hazlett et al, 2017), they are unlikely to be scalable or used universally in community-based settings. Third, there may be significant overlap between prodromal symptoms across neurodevelopmental disorders and child psychopathology more broadly (e.g., ASD, ADHD, anxiety) which may wax and wane across development (Begum Ali et al, 2020;Hatch et al, 2020;Miller et al, in press;Shephard et al, 2019), calling into question the specificity and longterm predictive validity of these tools and ultimately necessitating the shift to a transdiagnostic perspective.…”
Section: Measurement Challengesmentioning
confidence: 99%